Can a neutrino-dominated universe be rejected? - Melott, A. L. (The Astrophysical journal, 1985)
The clustering properties and large-scale motion in a standard neutrino-pancake model are shown to be consistent with observation for a steep primordial density perturbation spectrum. The autocorrelation properties of QSO Ly-alpha absorbers are shown to be consistent with the behavior of matter in numerical simulations of neutrino-dominated universes. The importance of beginning simulations at a highly linear stage is emphasized.